1989
DOI: 10.1128/aac.33.8.1247
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and characterization of dihydrofolate reductase from trimethoprim-susceptible and trimethoprim-resistant Pseudomonas cepacia

Abstract: Trimethoprim resistance was investigated in cystic fibrosis isolates of Pseudomonas cepacia. Determination of the MIC of trimethoprim for 111 strains revealed at least two populations of resistant organisms, suggesting the presence of more than one mechanism of resistance. Investigation of the antibiotic target, dihydrofolate reductase, was undertaken in both a susceptible strain and a strain with high-level resistance (MIC, >1,000 ,ug/ml). The enzyme was purified by using ammonium sulfate precipitation, gel f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

1991
1991
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(13 citation statements)
references
References 22 publications
(13 reference statements)
0
13
0
Order By: Relevance
“…A comparison of the kinetic properties of the DHFRs isolated from the two strains is shown in Table 2. The calculated K m and k cat values at pH 7.4 were essentially the same for the enzymes from the two isolates and similar to those of DHFRs from other species (3,40). S. maltophilia DHFR was strongly inhibited by MTX (inhibition constant [K i ], 18 pM for isolate 1), showing slow-binding inhibition (12) as described for the inhibition of DHFRs from other biological sources by this compound (38).…”
Section: Resultsmentioning
confidence: 62%
“…A comparison of the kinetic properties of the DHFRs isolated from the two strains is shown in Table 2. The calculated K m and k cat values at pH 7.4 were essentially the same for the enzymes from the two isolates and similar to those of DHFRs from other species (3,40). S. maltophilia DHFR was strongly inhibited by MTX (inhibition constant [K i ], 18 pM for isolate 1), showing slow-binding inhibition (12) as described for the inhibition of DHFRs from other biological sources by this compound (38).…”
Section: Resultsmentioning
confidence: 62%
“…Production of ␤-lactamases confers resistance to ␤-lactams [91], whilst a substantial outer membrane hydrophilic permeability barrier protects the bacillus from all hydrophilic antimicrobial agents [92]. Other mechanisms reported in the literature include production of modifying enzymes other than ␤-lactamases and alteration of antibiotic targets [91,93]. Apart from intrinsic mechanisms, acquired resistance has also been observed against commonly used antibiotics for infections caused by BCC and other common pathogens in CF patients.…”
Section: Evaluation Of the Available Clinical Evidencementioning
confidence: 93%
“…Purification of the enzyme from trimethoprim susceptible and trimethoprim resistant B. cepacia strains indicated that the protein from the resistant strain was indeed refractory to trimethoprim inhibition (Burns et al, 1989). While this finding is consistent with target alteration, the molecular and genetic basis for this reduced inhibition was not established.…”
Section: Burkholderia Cepacia Complex Organismsmentioning
confidence: 99%